Changing trends of maternal mortality with its causes- ten years retrospective study in a peripheral medical college of West Bengal, India - Dasgupta, Anjan; Pal, Abirbhab; ., Nikita; Dasgupta, Debanjana; Ghosh, Partha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The estimates of maternal mortality can only be used as a rough indicator of maternal health situation in any given country. High maternal mortality reflects not only in inadequacy of health care services for mothers, but also a low standard of living and socio economic status of the community. Objective was to assess the maternal mortality ratio (MMR), its probable causes and changing trends. Methods: The present study conducted at Midnapore Medical College (MMC), West Bengal. Data for analysis were collected from medical college record section and maternal death registrar book after having permission from higher authority of the college during the period from January 2009 to 2018 December. Total sample size for this period was 249. Statistical analysis was done through SPSS software. Results: Ten years data analysis of 249 subjects showed that total live births from January 2009 to December 2018 was 1,39,126 with MMR 178.97%. Hypertensive disorder of pregnancy (40.56%) was the leading direct cause of maternal death followed by hemorrhage (24.49%) and septicemia (10.84%). Heart disease (6.42%) was the major indirect cause of death followed by anemia (3.6%). Maternal death rate found high among primi gravida (59.43%) mothers and within 20 years age group (46.18%). Conclusions: Most maternal deaths are preventable by proper antenatal care, early diagnosis of high risk factors, timely referral to tertiary care centre along with community upliftment especially in rural and tribal based population.